(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Parameters of the correlation function and the spectral density ofa stationary ergodic random process of soil conditions heterogeneity along the pipeline are derived in the article. There are obtained values of the reliability level of the buried gas pipeline linear part by parameters of differental settlements and total longitudinal stresses. Keywords: random function of soil conditions heterogeneity, correlation function, spectral density, buried pipelines.